PERLINDUNGAN HUKUM TERHADAP KORBAN KEJAHATAN - Ony Rosifany (Universitas 17 Agustus 1945 Samarinda, 2017)
The problem of crime victims raises various problems in society in general and victims / victims of crime in particular.Legal protection for the community is very important because both groups and individuals can become victims or even as perpetrators of crime.Legal protection of crime victims as part of the protection of the people can be realized in various forms such as through restitution and compensation, medical services and legal aid.The protection of victims is an attempt to recover the losses suffered by the victims.